2007
DOI: 10.1007/s00294-006-0116-8
|View full text |Cite
|
Sign up to set email alerts
|

Roles of putative His-to-Asp signaling modules HPT-1 and RRG-2, on viability and sensitivity to osmotic and oxidative stresses in Neurospora crassa

Abstract: Neurospora crassa has a putative histidine phosphotransfer protein (HPT-1) that transfers signals from 11 histidine kinases to two putative response regulators (RRG-1 and RRG-2) in its histidine-to-aspartate phosphorelay system. The hpt-1 gene was successfully disrupted in the os-2 (MAP kinase gene) mutant, but not in the wild-type strain in this study. Crossing the resultant hpt-1; os-2 mutants with the wild-type or os-1 (histidine kinase gene) mutant strains produced no progeny with hpt-1 or os-1; hpt-1 muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
48
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 48 publications
1
48
0
Order By: Relevance
“…For rim15, only minor growth effects were detected upon deletion, while SSK1 affects sexual development and SSK1 and SKN7 are responsible for stress resistance (735). Comparable functions were found for N. crassa RRs (737,738).…”
Section: Protein Kinasesmentioning
confidence: 96%
“…For rim15, only minor growth effects were detected upon deletion, while SSK1 affects sexual development and SSK1 and SKN7 are responsible for stress resistance (735). Comparable functions were found for N. crassa RRs (737,738).…”
Section: Protein Kinasesmentioning
confidence: 96%
“…The ypdAϪ/ ypdAϩ heterokaryons show greater sensitivity to increased osmotic pressure, but not to H 2 O 2 , than the wild-type strain, indicating that YpdA is involved in the osmosensing signaling of A. nidulans (137). N. crassa has a Ypd1 homologue, named HPT-1 (histidine phosphotransfer protein 1), which also appears to be essential for viability because disruption of the hpt-1 gene is possible only in the os-2⌬ (Hog1 homologue) mutant background and not in the wild-type background (16). These data indicate that lethality caused by hpt-1 disruption is mediated through the Os-2 MAPK.…”
Section: The Two-component-like Phosphorelay Systemmentioning
confidence: 99%
“…6,16) Similarly, it has been reported that RRG-1 (an SskA ortholog) is involved in the osmotic stress response, 24) while a mutant of RRG-2 (an SrrA ortholog) exhibits no sensitivity to high osmotic conditions. 25) In the case of C. heterostrophus, Dic1 is responsible for osmotic adaptation, and the deletion mutants of RRs (Áchssk1 and Áchskn7) show moderate sensitivity to osmotic stress. 19,22,26) It has also been suggested that the RRs ChSsk1 and ChSkn7 additively contribute to osmotic adaptation.…”
mentioning
confidence: 99%